Serum IL-12 Is Increased in Mexican Obese Subjects and Associated with Low-Grade Inflammation and Obesity-Related Parameters. (20th February 2013) - Suárez-Álvarez, K.; Solís-Lozano, L.; Leon-Cabrera, S.; González-Chávez, A.; Gómez-Hernández, G.; Quiñones-Álvarez, M. S.; Serralde-Zúñiga, A. E.; Hernández-Ruiz, J.; Ramírez-Velásquez, J.; Galindo-González, F. J.; Zavala-Castillo, J. C.; De León-Nava, M. A.; et al.
Abstract : Interleukin-(IL-) 12 has been recently suggested to participate during development of insulin resistance in obese mice. Nevertheless, serum IL-12 levels have not been accurately determined in overweight and obese humans. We thus studied serum concentrations of IL-12 in Mexican adult individuals, examining their relationship with low-grade inflammation and obesity-related parameters. A total of 147 healthy individuals, 43 normal weight, 61 overweight, and 43 obese subjects participated in the study. Circulating levels of IL-12, tumor necrosis factor-alpha (TNF- α ), leptin, insulin, glucose, total cholesterol, and triglyceride were measured after overnight fasting in all of the study subjects. Waist circumference and body fat percentage were recorded for all the participants. Serum IL-12 was significantly higher in overweight and obese individuals than in normal weight controls. Besides being strongly related with body mass index (r = 0.5154 ), serum IL-12 exhibited a significant relationship with abdominal obesity (r = 0.4481 ), body fat percentage (r = 0.5625 ), serum glucose (r = 0.3158 ), triglyceride (r = 0.3714 ), and TNF- α (r = 0.4717 ). Thus, serum levels of IL-12 are increased in overweight and obese individuals and show a strong relationship with markers of low-grade inflammation and obesity in the Mexican adult population. Further research is needed to understand the role of IL-12 in developing obesity-associated alterations in humans.